Assessing the influence of diverse phosphorus sources on bacterial communities and the abundance of phosphorus cycle genes in acidic paddy soils - AFFI JEANNE, BONGOUA-DEVISME; ahya, KOUAKOU S.; Hippolyte, KOUADIO K.; LEMONOU MICHAEL, BAHAN F. (Frontiers in Microbiology, 2024)
The impact of chemical fertilizers on soil microbial communities is well acknowledged. This study assesses the influence of various phosphorus sources on soil bacterial composition, abundance, and Phosphorus Cycle Gene Abundance. Three phosphorus sources (natural phosphate rock, triple super phosphate (TSP), and chemical fertilizer NPK) were field tested following two rice cultivation cycles. Soil samples were subsequently collected and analyzed for bacterial groups and phosphorus cycle genes. Results indicated that the bacterial community composition remained consistent, comprising five main phyla: Firmicutes, Actinobacteria, Proteobacteria, Halobacterota, and Chloroflexia, regardless of fertilizer type. NPK fertilizer significantly reduced the relative abundance of Chloroflexia by 19% and Firmicutes by 16.4%, while increasing Actinobacteria and Proteobacteria by 27.5 and 58.8%, respectively. TSP fertilizer increased Actinobacteria by 27.1% and Halobacterota by 24.8%, but reduced Chloroflexia by 8.6%, Firmicutes by 12.6%, and Proteobacteria by 0.6%. Phosphate rock application resulted in reductions of Chloroflexia by 27.1%, Halobacterota by 22.9%, and Firmicutes by 6.2%, alongside increases in Actinobacteria by 46.6% and Proteobacteria by 23.8%. Combined application of TSP, NPK, and phosphate rock led to increases in Proteobacteria (24–40%) and Actinobacteria (13–39%), and decreases in Chloroflexia (5.2–22%) and Firmicutes (6–12.3%) compared to the control (T0). While the different phosphorus sources did not alter the composition of phosphorus cycle genes, they did modulate their abundance. NPK fertilizer did not significantly affect ppK genes (57–59%) but reduced gcd (100 to 69%), 3-phytase (74 to 34%), appA (91 to 63%), and phoD (83 to 67%). Phosphate rock reduced appA and gcd by 27 and 15%, respectively, while increasing 3-phytase by 19%. TSP decreased ppK and phoD by 42 and 40%, respectively, and gcd and appA by 34 and 56%, respectively. Combined fertilizers reduced appA (49 to 34%), 3-phytase (10 to 0%), and gcd (27 to 6%), while increasing ppK (72 to 100%). Among tested phosphorus sources, natural phosphate rock was best, causing moderate changes in bacterial composition and phosphorus genes, supporting balanced soil microbial activity. These findings highlight the complex interactions between fertilizers and soil microbial communities, underscoring the need for tailored fertilization strategies to maintain soil health and optimize agricultural productivity.